The Relationship Between Employees' Safety Knowledge on Slips and Falls at Workplace and Working Environment A Case Study in Malayan Sugar Manufacturing Co. Bhd (MSM), Prai - Muhamad Fauzi, Ibrahim (2012)
This study is about slips and falls at workplace which is focused on relationship between employees’ knowledge on slips and falls at workplace and working environment. This study also attempt to establish the safety programs for factories to reduce the slips and falls accident from occurring. This study was relatively limited studied focus on one company which is MSM, Prai. A questionnaire was developed and distributed for the purpose of data collection. 226 of responses were obtained from the 360 questionnaires that were distributed to respondents. Based on the correlation analysis it was found that all factors of environmental and workspace design, maintenance/ equipment, workers’ safety behaviours and management safety practices each made significant contribution independent variables. Hierarchically, the four independent variables are found to be among the strong variables to compliance with employees’ safety knowledge of slips and falls in this organization. Thus, some recommendation and implication future research and practice were also discussed in this research.